A study on biological rhythms of Himalayan yaks. Issue 7 (2nd October 2020) - Iqbal Yatoo, Mohd; Shabir, Mir; Kubrevi, Syed Shafat; Dar, Rukhsar Ahmad; Angmo, Kunzes; Kanwar, Maheshwar Singh; Bhat, Riyaz Ahmad; Muheet,; Parray, Oveas Raffiq
ABSTRACT: This study explores biological rhythms in Himalayan yaks. Indicators of reproductive, physiological rhythms and health were evaluated in 26 representative yaks from as many yak herds in 26 villages/hamlets of Changthang Ladakh (India). Average life span (20.57 ± 0.39 years), body weight (200–650 kg), age of puberty (2.1–2.9 years), oestrus period (21.1 ± 0.29 days), oestrus duration (16.9 ± 0.7 h), and gestation length (259.73 ± 1.48 days) was recorded. Seasonal breeding (spring/summer) with parturition cycle starting in spring season, was noticed. Single calving and singlet births were noted. Migration starts in April–May and returns in September–October. Common feeding practice includes pasture grazing. Hemoglobin (g/dl), packed cell volume (%), total erythrocytic count (x10 6 ) and total leucocytic count (x10 3 ) ranged from 12.29-14.56, 36.88-43.7, 7.28-7.79, and 8.43-7.15 during summer and winter, respectively. Rectal temperature (◦F) was 99.78-101.13, respiration rate (breaths per minute) was 34.23-65.38 and heart rate (beats per minute) was 68.65-99.04 during winter and summer, respectively. Seasonal cyclicity of common infectious and non-infectious diseases was noted. In conclusion, this study provides baseline data of biological rhythms of yaks and elaborates their seasonal variation with emphasis on future management prospects.